The Political Economy of Financial Fragility - Erik Feijen; Enrico Perotti (Tinbergen Institute, 2005)
While financial liberalization has in general favorable effects, reforms in countries with poor regulation is often followed by financial crises. We explain this variation as the outcome of lobbying interests capturing the reform process. Even after liberalization, market investors must rely on enforcement of investor protection, which may be structured so as to block funding for new entrants, or limit their access to refinance after a shock. This forces inefficient default and exit by more leveraged entrepreneurs, protecting more established producers. As a result, lobbying may deliberately worsen financial fragility. After large external shocks, borrowers from the political elite in very corrupt countries may successfully lobby for weak enforcement, and retain control of collateral. We provide evidence that industry exit rates and profit margins after banking crises are higher in the most corrupt countries.
Keywords: G21; G28; G32; 330; Politics; Lobbying; Financial Development; Investor protection